Virtualisasi Server Private Cloud Storage Dengan Owncloud 8.1.3 Pada Ubuntu 14.04 Lts - Syarifuddin, Yayat; , Helman Muhammad, S.T.,M.T (2016)
One of the technologies that is booming as it is today is a cloud computing system are often known by the name "cloud computing" . One part of this cloud computing technology is media data sharing , better known by the name "cloud storage" . The present study aimed to design a system based on Ubuntu 14:04 server that is configured to manufacture the cloud. By using APCU application , a server in the optimization so that the performance will become lighter . Based on the results of comparative testing RAM usage between systems with APCU systems without APCU , data showed that the system has APCU average process which is lower by 43.75 % compared to the system without having a process APCU average of 48.5 % .